Alterações na dieta de peixes associados ao cultivo de tilápias em tanques-rede no reservatório de Rosana, rio Paranapanema. - Demetrio, Jose Antonio (2010)
This study evaluated the effects of tilapia cultivation in net cages on the diet of associated wild ichthyofauna in the Corvo River, Rosana Reservoir, Paranapanema River. It identified the direct and indirect effects of different protein levels in spare feed inside the net cages on the distribution and abundance of fish in adjacent areas, taking into account the specific variations in natural food and artificial feed intake. The recording of different results established by control data and variations in protein content for the cultivation reveals the alimentary content of the dominant species to an extent that altered not only the intake pattern of the associated fish assemblage but also intensified artificial feed absorption. The introduction of organic matter also led to the proliferation of microcrustaceans, abrupt oscillations in the composition of food items, with distinct variations among species, thus expanding trophic levels of ichthyofauna in the cultivation area. Artificial feed altered the food intake pattern of the fish assemblage associated with cultivation in net cages, expanding feeding intensity, as measured by stomach fullness levels. Changes in diet for the artificial feed were more evident in four of the eight dominant species of the fish assemblage, among them P.maculatus and I.labrosus, as they were related to the proximity of the net cages and the background environment. The volumes and occurrences of items recorded by the food index (IAi) showed a large intake of zooplankton, aquatic insects and feed. Dominant species Auchenipterus osteomystax, Steindachnerina brevipinna, Iheringichthys labrosus, Loricariichthys platymetopon, Plagioscion squamosissimus, Pimelodus maculatus, Metynnes maculatus and Satanoperca pappaterra, on a percentage basis, ingested more aquatic insects than terrestrial insects, algae, detritus, sediment, decapods, plants and feed. The frequency of occurrence and stomach volume from one phase to another highlights the increasing presence of feed, insects, and microcrustaceans. Peculiarities involving the type of feed, distance, the background environment and participation of species groups marked the influence of net cages.